Metafora Konseptual dalam Majalah Niponica No. 33: Nihon No Bunka Wo Tabisuru - Barrera, Marco Antonio; Oeinada, I Gede; Purnawati, Ketut Widya (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 7 No 1 (2025)DO - 10.24843/JS.2025.v07.i01.p10, 2025)
This study is titled "Conceptual Metaphor in Niponica Magazine No.33: Nihon no Bungaku wo Tabisuru." Conceptual metaphor is a form of mental construction derived from human experience. The features of metaphors are generally found in various informational media aimed at conveying information to be well understood. This study aims to describe conceptual metaphors in Niponica Magazine No.33. The method used in this research is descriptive qualitative analysis, with the theory applied being the conceptual metaphor theory by Lakoff & Johnson (1980) and the image schema theory by Croft & Cruse (2004). Based on the findings, there are three types of metaphors in a total of 13 data points: 4 structural metaphor data points, 4 orientational metaphor data points, and 5 ontological metaphor data points. There are 5 types of image schemas: Existence, Unity, Identity, Container, and Force. The use of metaphors in magazine writing not only serves as decoration but also deepens the understanding of the concepts conveyed.